2019
DOI: 10.1002/jso.25407
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor beta expression correlates with proliferation in desmoid tumors

Abstract: Background and objectives Estrogen receptor signaling and cyclin D1 have a major role in tumor cell proliferation in breast cancer. Desmoid tumors are rare neoplasms that may respond to endocrine treatment. The present study aimed to investigate the expression levels and the clinical relevance of estrogen receptor beta (ERβ) and cyclin D1 in desmoid tumors. Methods This study consists of 83 patients with a surgically treated desmoid tumor. ERβ and cyclin D1 expression was examined by immunohistochemistry in ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 18 publications
1
23
0
3
Order By: Relevance
“…Alternations in estrogenic signaling pathways, as well as ERβ expression, have been discussed in the context of physiological and pathological processes, such as maintenance of the bone marrow microenvironment [ 11 ], neuronal-mediated contractions of the gastrointestinal tract [ 12 ], recovery of reproductive system injury [ 13 ], anxiolytic effects [ 14 ], and diseases such as Parkinson’s disease [ 15 ], endometriosis [ 16 ], myocardial infarction [ 17 ] and type 2 diabetes [ 18 ]. Moreover, ERβ has been shown to participate in the pathological process of various cancers, including uterine leiomyomas [ 19 ], colorectal cancer [ 20 ], desmoid tumors [ 21 ], prostate cancer [ 22 ] and duct carcinoma [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternations in estrogenic signaling pathways, as well as ERβ expression, have been discussed in the context of physiological and pathological processes, such as maintenance of the bone marrow microenvironment [ 11 ], neuronal-mediated contractions of the gastrointestinal tract [ 12 ], recovery of reproductive system injury [ 13 ], anxiolytic effects [ 14 ], and diseases such as Parkinson’s disease [ 15 ], endometriosis [ 16 ], myocardial infarction [ 17 ] and type 2 diabetes [ 18 ]. Moreover, ERβ has been shown to participate in the pathological process of various cancers, including uterine leiomyomas [ 19 ], colorectal cancer [ 20 ], desmoid tumors [ 21 ], prostate cancer [ 22 ] and duct carcinoma [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin D1 and c-Myc signalling is commonly deregulated in tumourigenesis due to their promotional effects on cell proliferation by enhancing the G1 to S-phase transition of the cell cycle [ 34 , 35 ]. Cyclin D1 was overexpressed in at least 40% of DTF cases [ 26 , 27 , 29 , 36 ]. Two studies found a significant correlation between β-catenin nuclear expression and cyclin D1 overexpression (Fisher’s exact test, p = 0.029; Fisher’s exact test, p = 0.034, respectively) [ 27 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, three studies demonstrated significantly higher CCND1 gene expression in the mutated CTNNB1 group compared with the wild-type group ( χ 2 test, p = 0.038; Mann–Whitney U test, p = 0.019; Mann–Whitney U test, p = 0.0120, respectively) [ 26 , 29 , 31 ]. Saito et al and Santti et al demonstrated significant cellular proliferative activity in DTF cases with cyclin D1 overexpression via a proliferating cell nuclear antigen-labelling index (Fisher’s exact test, p = 0.004) and Ki-67 ( r = 0.40, p = 0.001), respectively [ 27 , 36 ]. These findings suggest aberrant Wnt/β-catenin signalling may exert its proliferative effects through the overexpression of positive cell-cycle regulatory proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Santti et al [24] have found a trend in very high ERβ expression to predict a higher risk of relapse. In our recurrent cases primary biopsy samples demonstrated high range ERβ positivity, which decreased in the rebiopsy samples even to a complete loss of expression.…”
Section: N) -Nuclear Positivity; (C) -Cytoplasmic Positivity; (M) -Membranous Positivity; --Negative Staining; +/--Weak; Focal Staining; mentioning
confidence: 99%